Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the following system of equations using the substitution method:
[tex]\[ \left\{\begin{array}{l} y = -3x - 4 \\ 9x + 3y = -12 \end{array}\right. \][/tex]
Follow these steps:
1. Substitute [tex]\( y \)[/tex] in the second equation:
Given the first equation [tex]\( y = -3x - 4 \)[/tex], we substitute [tex]\( y \)[/tex] into the second equation [tex]\( 9x + 3y = -12 \)[/tex].
[tex]\[ 9x + 3(-3x - 4) = -12 \][/tex]
2. Simplify the equation:
Distribute the 3 into the terms inside the parentheses.
[tex]\[ 9x + 3(-3x) + 3(-4) = -12 \implies 9x - 9x - 12 = -12 \][/tex]
3. Combine like terms:
This simplifies to:
[tex]\[ 9x - 9x - 12 = -12 \implies -12 = -12 \][/tex]
Notice that the variable terms [tex]\( 9x \)[/tex] and [tex]\( -9x \)[/tex] cancel each other out, leaving just [tex]\(-12 = -12\)[/tex], which is a true statement.
4. Interpret the result:
Since the final equation [tex]\(-12 = -12\)[/tex] is always true, it indicates that the system of equations has an infinite number of solutions.
5. Express the solutions in terms of [tex]\( x \)[/tex]:
We can express the solutions in the form of [tex]\( y = -3x - 4 \)[/tex] where [tex]\( x \)[/tex] can be any real number. Thus, the solutions are pairs [tex]\((x, y)\)[/tex] that satisfy this relationship.
The solutions to the system of equations are:
[tex]\[ \boxed{\text{infinite solutions in the form } (x, -3x - 4)} \][/tex]
[tex]\[ \left\{\begin{array}{l} y = -3x - 4 \\ 9x + 3y = -12 \end{array}\right. \][/tex]
Follow these steps:
1. Substitute [tex]\( y \)[/tex] in the second equation:
Given the first equation [tex]\( y = -3x - 4 \)[/tex], we substitute [tex]\( y \)[/tex] into the second equation [tex]\( 9x + 3y = -12 \)[/tex].
[tex]\[ 9x + 3(-3x - 4) = -12 \][/tex]
2. Simplify the equation:
Distribute the 3 into the terms inside the parentheses.
[tex]\[ 9x + 3(-3x) + 3(-4) = -12 \implies 9x - 9x - 12 = -12 \][/tex]
3. Combine like terms:
This simplifies to:
[tex]\[ 9x - 9x - 12 = -12 \implies -12 = -12 \][/tex]
Notice that the variable terms [tex]\( 9x \)[/tex] and [tex]\( -9x \)[/tex] cancel each other out, leaving just [tex]\(-12 = -12\)[/tex], which is a true statement.
4. Interpret the result:
Since the final equation [tex]\(-12 = -12\)[/tex] is always true, it indicates that the system of equations has an infinite number of solutions.
5. Express the solutions in terms of [tex]\( x \)[/tex]:
We can express the solutions in the form of [tex]\( y = -3x - 4 \)[/tex] where [tex]\( x \)[/tex] can be any real number. Thus, the solutions are pairs [tex]\((x, y)\)[/tex] that satisfy this relationship.
The solutions to the system of equations are:
[tex]\[ \boxed{\text{infinite solutions in the form } (x, -3x - 4)} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.